(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The most important element of economic security in modern conditions is financial safety. In modern conditions the impact of geofinances, the world’s financial systems on the individual state moves to a qualitatively new level. According to the dominant position occupied by a financial component in today’s economy, the authors can characterize the last one as an economy controlled by the basis of their financial way, through financial mechanisms, using financial leverage, financial incentives and fiscal purposes. In this article, financial security is considered by the example of developing countries - members of the Shanghai Cooperation Organization in Kazakhstan, Russia and China.